An analytical study of the Shariah rulings and contemporary issues regarding online marriage in the light of Hanafi jurisprudence - Dr. Muhammad Zakariya (Journal of Religion and Society, 2025)
This study examines the Shariah decision and more current questions that pertain to online marriage in the context of Hanafi jurisprudence. The era of fast technological development has impacted all spheres of human life, and made an imprint on social and legal relations. Marriage online as a digital development of traditional contracts has become an important matter which needs to be studied by scholars. The paper identifies these requirements of Nikah in Hanafi fiqh- Ijab (offer), Qubul (acceptance), Witnesses, consent of the guardian (wali) and mahr (dower), and examines whether they are possible via online sites. Although Hanafi jurisprudence allows marriage based on writing or agency or indirect communication, modern problems including verification of identity, fraud, witness validity, and registration are distinctive. The methodology of the research is tahlili (analytical), taqwimi (evaluative) and taqabili (comparative). Primary sources (al-Hidayah, Bada’i al-Sana, Radd al-Muhtar) and modern academic views and case studies of the law have been used. Other Sunni schools of law (Shafi, Maliki, and Hanbali) and modern fatwas of South Asia and the Arab world are also incorporated. Results reveal that in line with Hanafi jurisdiction, online marriage is a valid marriage as long as the required conditions of Nikah are met under the law and religion. Nevertheless, caution has to be observed to avoid fraud, misrepresentation and transgressing on Shariah limits. The analysis has found that online marriage is not a proper alternative to the traditional Nikah ceremonies, but it may be adopted as a valid option when it comes to the necessity, e.g., in case of pandemics, long-distance relationships, or legal limitations. The study also advises effective legal principles, verified online platforms and standard procedures to achieve transparency, protect rights and harmonize the principles of Shariah with modern requirements. Keywords: Online Nikah, Hanafi Jurisprudence, Shariah Rulings, Islamic Family Law, Contemporary Fiqh Issues.